The impact of population displacement due to river bank erosion on the education of erosion victims: a study in jangipur sub-division of murshidabad district, West Bengal, India - Ghosh, Dr. Debika; Sahu, Dr. Abhay Sankar (Bulletin of Geography. Socio-economic Series, 2019)
The present research aims to find out whether population displacement due to river bank erosion has any impact on education of the erosion victims of the developing countries or not. To fulfil the objective of the study, 19 erosion affected study units were selected along the banks of the Ganga-Bhagirathi river in the Jangipur sub-division of Murshidabad district, West Bengal. Pearson’s correlation analysis and multiple linear regression analysis were performed using SPSS software. The result of the study shows that frequency of population displacement due to bank erosion and percentage of child labour are positively and significantly correlated (r = 0.51). A low mean year of schooling has been observed in almost all selected study units. The result of multiple linear regression analysis shows that river bank erosion has an adverse impact on the education of the people living along the river banks.